CONTROL OF THE FALL ARMYWORM OF MAIZE - OSORIO A, FRANCISCO J; MC KELVEY, JJ (Hospital General, CD MEXICO, DF, MEX, 1900)
A 1% to 01% dibromide concn gives maximum fungicidal and fungistatic effectiveness Use on stored grains only is recommended; plants are damaged
PHYS REV B
Keywords: CONTROL, FALL ARMYWORM, MAIZE; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL